The first representative of newly-recorded genus of the ganodermataceae in Cat Tien national park, Dong Nai, Lam Dong province, Vietnam: Humphreya endertii - Tham, Le Xuan; Quoc Hung, Nguyen Le; Duong, Pham Ngoc; Moncalvo, J. M. (Academia Journal of Biology, 2012)
The first representative of the genus Humphreya Stey. newly-found in National Park of Cat Tien, South Vietnam, were identified and described as following: Humphreya endertii Stey. Pileus stipitate, single, woody, also coriaceous-woody, applanate to central-depressed, orbicular or kidney shape, 3.6-11.5 cm in diam.; concentrically zonate and sulcate to rugose or smooth, variously radially plicate or concentrically wrinkled; margin acute to obtuse, sometimes deflexed, regular to undulate as many glossy plicates growing over each others, so that thickened. Pilear cover opaque, red brown, red coffeate or yellow brown. The crust on the upper surface of pileus red brown - red coffeate, glossy-laccate at first, but later becoming dull by spore dusts covering on, thin, easily broken when craking or pressing with fingers. The crust of the stipe thicker, more laccate, shiningly glossy red brown. The stipes long to very long (7.5-17.5 cm), cylindric (0.7-1.4 cm in diam.). The context thick 0.3-0.8 cm, up to > 1.1 cm in base part, creamy fleshy, composed of trimitic hyphae. The tube layer quite thick (0.5-0.9 cm), grey creamy or pale cinnamon. Pores round or angular, small (4-5/mm) with the surface creamy or pale grey or dark grey when touched. The spores typically ganodermoid, honey yellow, medium sized 12.5-16.5 ´ 9.5-11.5 mm, truncate - ovate with an yellow round guttule in the center. The spore surface coarse reticulate (labirynth architecture) with very thick column layer from inner wall (up to 2.5 mm). The hyaline apex (germpore - aperture) very thick, concave or convex, opposite to the hilum on the bottom (the attachments of spores to sterigmata). Humphreya endertii was recorded only from type locality (Indonesia), in Malaysia and now found in South Vietnam. In general, macro and micro-morphological characteristics of four representatives designated to Humphreya are dissolved in many groups of Ganoderma species with intermediate or transient taxa, particularly their ganodermoid basidiospore type and thus they should not be isolated as a distinct genus, but ranked as a subgenus or section in the genus Ganoderma Karst. The germs were isolated and purified on PGA media for molecular examinations to support our discussions and for fruitful cultivations on mixed substrates to supply of materia medica.